La diversité des capitalismes latino-américains : les cas de l’Argentine, du Brésil et du Mexique - Ilán Bizberg; Bruno Théret (Revue de la Régulation)
This article analyses the way in which different socio-political configurations have had a significant effect on the economic development of Argentina, Brasil and Mexico. The characteristics of the socio-political coalitions in the three countries are presented, and their imprints on industrial relationships, monetary and financial systems, and the organizational structures of the State are studied. In conclusion, it is suggested that the observed differences in the three countries in the degrees of autonomy of the State, and the organizational forces of the unions and of the entrepreneurs define different economic patterns and forms of insertion in the international economy that allow to speak of a diversity of capitalisms genuine to Latin America.